The ride of her life eaudiobook The true story of a woman, her horse, and their last-chance journey across america. - Letts, Elizabeth (Random House Audio, 2021)
NATIONAL BESTSELLER • The #1 New York Times bestselling author of The Perfect Horse and The Eighty-Dollar Champion presents a “heartwarming [and] engaging folk-hero biography” ( Kirkus Reviews ) of a woman who fulfilled her lifelong wish to see the Pacific Ocean by riding her horse across America. “[Letts] vividly portrays an audacious woman whose optimism, courage, and good humor are to be marveled at and admired.”— Booklist , starred review In 1954, sixty-three-year-old Maine farmer Annie Wilkins embarked on an impossible journey. She had no money and no family, she had just lost her farm, and her doctor had given her only two years to live. But Annie wanted to see the Pacific Ocean before she died. She ignored her doctor’s advice to move into the county charity home. Instead, she bought a cast-off brown gelding named Tarzan, donned men’s dungarees, and headed south in mid-November, hoping to beat the snow. Annie had little idea what to expect beyond her rural crossroads; she didn’t even have a map. But she did have her ex-racehorse, her faithful mutt, and her own unfailing belief that Americans would treat a stranger with kindness. Annie, Tarzan, and her dog, Depeche Toi, rode straight into a world transformed by the rapid construction of modern highways. Between 1954 and 1956, the three travelers pushed through blizzards, forded rivers, climbed mountains, and clung to the narrow shoulder as cars whipped by them at terrifying speeds. Annie rode more than four thousand miles, through America’s big cities and small towns. Along the way, she met ordinary people and celebrities—from Andrew Wyeth (who sketched Tarzan) to Art Linkletter and Groucho Marx. She received many offers—a permanent home at a riding stable in New Jersey, a job at a gas station in rural Kentucky, even a marriage proposal from a Wyoming rancher. In a decade when car ownership nearly tripled, when television’s influence was expanding fast, when homeowners began locking their doors, Annie and her four-footed companions inspired an outpouring of neighborliness in a rapidly changing world.